(untitled) (World Bulletin of Social Sciences, 2026)
This article provides a comprehensive analysis of the history of cultural and artistic cooperation between the Republic of Uzbekistan and the Republic of Austria and the Swiss Confederation. The study examines the initial cultural interactions established in the early 1990s within the framework of the Commonwealth of Independent States (CIS), as well as initiatives proposed by Austria and the development of applied arts and exhibition activities with Switzerland, which contributed to the formation of cultural diplomacy. The research also explores the development of cultural relations at both institutional and individual levels, particularly through the activities of Chingiz Aitmatov, the participation of folk artisans in the international arena, and the entry of handicraft products into European markets. The findings demonstrate that cooperation with Austria and Switzerland played a significant role in Uzbekistan’s integration into the global cultural space.